2014
DOI: 10.1098/rspb.2014.0276
|View full text |Cite
|
Sign up to set email alerts
|

Fitness consequences of environmental conditions at different life stages in a long-lived vertebrate

Abstract: The predictive adaptive response (PAR) hypothesis proposes that animals adjust their physiology and developmental trajectory during early life in anticipation of their future environments. Accordingly, when environmental conditions in early life match environmental conditions during adulthood, individual fitness should be greater. Here, we test this hypothesis in a longlived mammal, the roe deer, using data from two contrasting populations, intensively monitored for more than 35 years. In the highly productive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 59 publications
(114 reference statements)
11
91
1
Order By: Relevance
“…This might explain why studies that support the environment-matching hypothesis tend to be of fast-developing species (e.g. Oksanen et al, 2012;Saastamoinen et al, 2010) rather than those that develop slowly (Douhard et al, 2014;Hayward et al, 2013). However, given the small number of studies carried out so far, more work is needed to examine this further.…”
Section: Discussionmentioning
confidence: 94%
“…This might explain why studies that support the environment-matching hypothesis tend to be of fast-developing species (e.g. Oksanen et al, 2012;Saastamoinen et al, 2010) rather than those that develop slowly (Douhard et al, 2014;Hayward et al, 2013). However, given the small number of studies carried out so far, more work is needed to examine this further.…”
Section: Discussionmentioning
confidence: 94%
“…(Online version in colour. ) rspb [26,[38][39][40][41][42]. However, the fitness crossover sought was not the one shown in figure 2.…”
Section: Empirical Tests Of Adaptive Developmental Plasticitymentioning
confidence: 95%
“…This is something that can be tested in systems where long-term, individual-based ecological datasets are available [26].…”
Section: Comparing Informational and Somatic State-based Hypothesesmentioning
confidence: 99%
“…Furthermore, mean fitness of females that experienced poor environmental conditions in early life was comparable to that of females exposed to more favourable conditions. Many studies have shown that individuals born in poor environmental conditions are at permanent reproductive disadvantage regardless of their adult environment [21,22,25,58], the so-called reverse silver spoon effect [12,13]. However, such effects are not universal in food-limited environments.…”
Section: Discussionmentioning
confidence: 99%